GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2017)
A dataset containing 3671 species occurrences available in GBIF matching the query: TaxonKey: Ostrya J. Hill, 1757 Geometry: POLYGON((-23.203125 53.748710,-23.203125 25.799891,68.203125 25.799891,68.203125 53.748710,-23.203125 53.748710)) or POLYGON((224.296875 65.072130,224.296875 -11.867350,319.921875 -11.867350,319.921875 65.072130,224.296875 65.072130)) or POLYGON((77.343749 46.558860,77.343749 -2.811371,157.5 -2.811371,157.5 46.558860,77.343749 46.558860)) HasGeospatialIssue: false HasCoordinate: true. The dataset includes 3671 records from 108 constituent datasets: 9 records from Bioimages. 18 records from Marie-Victorin Herbarium (MT) - Plantes vasculaires. 3 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 4 records from University of Vienna, Institute for Botany - Herbarium WU. 1 records from IAC - Herbário do Instituto Agronômico de Campinas. 4 records from Naturalis Biodiversity Center (NL) - Botany Leiden. 1 records from Plant Specimen in Yunnan, China from Herbarium (PE),Institute of Botany, Chinese Academy of Sciences. 1 records from Harriet Irving Botanical Gardens (HIBG). 27 records from Herbier Louis-Marie (QFA) - Collection de plantes vasculaires. 26 records from Plant Specimen Database of Tama Forest Science Garden, Forestry and Forest Products Research Institute, Japan. 1 records from MBM - Herbário do Museu Botânico Municipal. 3 records from Données ONF Faune-Flore-Fonge. 1 records from Australia's Virtual Herbarium. 1 records from Kathryn Kalmbach Herbarium. 208 records from iNaturalist Research-grade Observations. 59 records from CONN. 7 records from H.A. Stephens Herbarium. 8 records from LSU Shirley C. Tucker Herbarium at Louisiana State University - Vascular Plants. 1 records from Collection botanique Le Grand A. (BOUM). 6 records from Herbarium of the Department of Natural Forests (Forest Research Institute). 1 records from Zielbach (Töll). 17 records from naturgucker. 1 records from Naturpark Kottenforst-Ville Sammelaktion 15.-19.6.. 1 records from Aktion - Friedensburg Oberschule. 1 records from Naturpark Kottenforst-Ville 15.6.09. 4 records from MfN - Fossil plants (Cenophytic). 2077 records from INPN - Données flore des CBN agrégées par la FCBN. 5 records from The Fungal Collection at the Senckenberg Museum für Naturkunde Görlitz. 71 records from Herbario XAL del Instituto de Ecología, A.C., México (IE-XAL). 48 records from Herbario IEB del Instituto de Ecología, A.C., México (IE-BAJíO). 2 records from FKSE-Herbarium specimens of Faculty of Symbiotic Systems Science, Fukushima University, Japan. 13 records from Royal Botanic Garden Edinburgh Living Plant Collections (E). 29 records from Angiospermatatophytina Collection of Saitama Museum of Natural History. 12 records from Tiroler Landesmuseum Ferdinandeum. 186 records from Tropicos Specimen Data. 12 records from Natural History Museum (London) Collection Specimens. 1 records from Natural History Museum, Vienna - Herbarium W. 3 records from Diversidad vegetal en un gradiente en la Sierra Madre Occidental: flora y vegetación de la Región de San Javier y Yécora, Sonora. 2 records from Inventario florístico de la Sierra de San Carlos, Tamaulipas. 2 records from Inventario florístico de la Frailescana (zona focal), Chiapas, México. 8 records from Florística y biogeografía de algunos bosques mesófilos de la Huasteca Hidalguense: Fase II (Tlahuelompa y Eloxochitlán). 1 records from Lista florística preliminar de Tamaulipas. 2 records from Florística y biogeografía de algunos bosques mesófilos de la Huasteca Hidalguense: Fase 3 (Chapulhuacán y Pisaflores). 4 records from Base de datos de las regiones prioritarias 113 y 120 en los municipios de Zirándaro y Coahuayutla, (Guerrero). 4 records from Flora del Parque Nacional Cumbres de Monterrey, Nuevo León, México. 3 records from Historia natural del parque ecológico estatal de Omiltemi, Chilpancingo, Guerrero, México. 52 records from Karl Franzens University of Graz, Insitute for Botany - Herbarium GZU. 3 records from Inventario florístico y base de datos de la Reserva Ecológica Sierra de San Juan, Nayarit, México. 1 records from Catálogos florísticos de México por entidad federativa e información etnobotánica de la Colección del Herbario Nacional Biól. Luciano Vela Gálvez (INIF). 15 records from Recuento de la diversidad florística de Veracruz. 2 records from Base de datos sobre la flora de Durango. 3 records from Catálogo y base de datos preliminar de la flora de Sinaloa. 1 records from Universität Salzburg. 1 records from Canadian Museum of Nature Herbarium. 5 records from Colección de plantas vasculares del herbario de la Universitat de València (VAL).. 2 records from Herbario de Plantas Vasculares de la Universidad de Salamanca: SALA. 9 records from Real Jardín Botánico (Madrid), Vascular Plant Herbarium (MA). 4 records from Aranzadi Zientzi Elkartea. 1 records from CIBIO, Alicante:ABH-GBIF. 3 records from Herbario de la Universidad de Sevilla. 1 records from Herbario HSS Finca La Orden-Valdesequera (CICYTEX). Gobierno de Extremadura. 1 records from Botanic Garden of the Finnish Museum of Natural History. 53 records from Paleobiology Database. 5 records from Plant Specimens of Kurashiki Museum of Natural History. 43 records from Herbarium (UNA). 1 records from Herbarium Willing. 1 records from PonTaurus collection. 2 records from Observations du Conservatoire botanique national du Bassin parisien.. 5 records from United States National Plant Germplasm System Collection. 1 records from The Erysiphales Collection at the Botanische Staatssammlung München. 1 records from The Erysiphales Collection at the University Halle-Wittenberg. 6 records from Herbarium de Geo. B. Hinton, México. 4 records from Vascular Plants Collection of Sagamihara City Museum. 2 records from Kochi Prefectural Makino Botanical Garden. 2 records from Herbario de la Universidad de Arizona, EUA. 18 records from Repatriación de datos del Herbario de Arizona (ARIZ). 102 records from FloVegSI - Floristical and fitocenological database of ZRC SAZU. 1 records from Schlern - (Bozen). 1 records from Plantae, TAIF (Taiwan e-Learning and Digital Archives Program, TELDAP). 3 records from Base de datos de plantas vasculares del País Vasco: ARAN-EH. 47 records from Field Museum of Natural History (Botany) Seed Plant Collection. 1 records from Phragma-Thermis/Thessaloniki. 91 records from R. L. McGregor Herbarium Vascular Plants Collection. 38 records from Vascular Plant Specimen Database of Kanagawa Prefectural Museum of Natural History. 22 records from Gunma Museum of Natural History, Vascular Plant Specimen. 1 records from Artenvielfalt am Schlern. 2 records from Botany Division, Yale Peabody Museum. 6 records from Paleobotany Division, Yale Peabody Museum. 1 records from MEXU/Flora de Oaxaca. 1 records from VIT Herbarium - Vascular Plants (The Natural History Museum of Alava). 4 records from Lund Botanical Museum (LD). 10 records from Geographically tagged INSDC sequences. 2 records from Plant Specimen from Herbarium (LBG) in China, Lushan Botanical Garden, Jiangxi and Chinese Academy of Sciences. 2 records from University of Manitoba Herbarium (WIN) - Vascular Plant Collection. 5 records from The fossil collection (F) of the Muséum national d'Histoire naturelle (MNHN - Paris). 6 records from Plant Specimen from Herbarium (IBK) in China, Guangxi Institute of Botany, Chinese Academy of Sciences. 4 records from Royal Botanic Garden Edinburgh Herbarium (E). 2 records from Michigan State University Herbarium Vascular Plants. 4 records from Herbier du Québec (QUE) – Collection de plantes vasculaires. 9 records from University of British Columbia Botanical Garden Collections (UBCBG). 3 records from Données ONF Faune-Flore-FOnge. 31 records from The New York Botanical Garden Herbarium (NY) - Vascular Plant Collection. 47 records from Green Plant Herbarium (TRT). 50 records from E. C. Smith Herbarium (ACAD). 3 records from SysTax - Herbaria. 15 records from Geneva Herbarium – General Collection (G). 2 records from Nijmegen Natural History Museum (NL) - Herbarium. 8 records from CAS Botany (BOT). Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences